2016
DOI: 10.1038/srep30398
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation of spiral-like patterns with distinct periodic physical properties by confined electrodeposition of Co-In disks

Abstract: Spatio-temporal patterns are ubiquitous in different areas of materials science and biological systems. However, typically the motifs in these types of systems present a random distribution with many possible different structures. Herein, we demonstrate that controlled spatio-temporal patterns, with reproducible spiral-like shapes, can be obtained by electrodeposition of Co-In alloys inside a confined circular geometry (i.e., in disks that are commensurate with the typical size of the spatio-temporal features)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Notwithstanding the large corpus of systems investigated, recently reviewed in Bozzini et al and Krastev et al, still the mechanisms governing the spatiotemporal organization during electrochemical phase formation are poorly understood. Electrodeposition studies (for a comprehensive list of references, see Bozzini et al) have initially dealt with a range of Ag alloys (Ag–Sb, Ag–Sn, Ag–In, Ag–Bi, Ag–Cd), but it has been recently shown that similar phenomena also occur with Bi, In and Sb alloys not involving Ag: Ni–P–W–Bi, Au–In, Co–In, , Pd–In, Cu–Sb . Moreover, alloys with Pt-group metals, as Ir–Ru and Pt–Ir, electrodeposited from molten salts, have been found to exhibit the same type of dynamic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the large corpus of systems investigated, recently reviewed in Bozzini et al and Krastev et al, still the mechanisms governing the spatiotemporal organization during electrochemical phase formation are poorly understood. Electrodeposition studies (for a comprehensive list of references, see Bozzini et al) have initially dealt with a range of Ag alloys (Ag–Sb, Ag–Sn, Ag–In, Ag–Bi, Ag–Cd), but it has been recently shown that similar phenomena also occur with Bi, In and Sb alloys not involving Ag: Ni–P–W–Bi, Au–In, Co–In, , Pd–In, Cu–Sb . Moreover, alloys with Pt-group metals, as Ir–Ru and Pt–Ir, electrodeposited from molten salts, have been found to exhibit the same type of dynamic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…There are the strong relationships between the pattern structure and the experimental conditions such as the applied potential, concentration of chemicals, and type of complex agents . Also, recent studies experimentally show that the spatiotemporal patterns emerge on microdiscs and spherical electrodes as well as mm-sized flat electrodes. Therefore, the self-organization process is versatile in terms of the controllability of the material structure and the abundant choice of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of materials with novel physicochemical properties employing the controlled manipulation of their microstructure at the atomic level became a field based on solid-state chemistry. , As recently proposed, nevertheless, self-organization under far from equilibrium conditions can also be utilized as a promising and alternative synthetic method to create more complex materials in terms of structure and composition. Differently from a standard step-by-step synthesis procedure, self-organized electrochemical structures arise without any external control or template-based support . Nanostructured metallic multilayers, magnetic nanopatterning, switchable roughness surfaces, and porous nanoarrays are a few examples found through the use of this nonequilibrium synthetic method. Followed by the spontaneous assembly of the material constituents, temporal instabilities, such as excitability, multistability, and oscillations, are observed on the main variables that describe the system .…”
Section: Introductionmentioning
confidence: 99%
“…3−7 Differently from a standard step-by-step synthesis procedure, self-organized electrochemical structures arise without any external control or template-based support. 8 Nanostructured metallic multilayers, 9 magnetic nanopatterning, 10 switchable roughness surfaces, 11 and porous nanoarrays 12 are a few examples found through the use of this nonequilibrium synthetic method. Followed by the spontaneous assembly of the material constituents, temporal instabilities, such as excitability, multistability, and oscillations, are observed on the main variables that describe the system.…”
Section: Introductionmentioning
confidence: 99%